Cyber arbitration as a dispute resolution mechanism in the growing electronic commerce in colombia - Andres Camilo Laino Cruz; Camila Andrea Bohórquez Rueda (Postulados: Revista Sociojurídica)
The present resear ch seeks to study and analyze the possibility of implementing Electr onic Arbitration or Cyber Arbitration as an ideal mechanism to resolve disputes ar ising f rom the growing rise of electr onic commer ce in Colombia based on the compar ison of the guidelines on the matter that have been issued by countries belonging to the Andean Community of Nations (C AN). Electr onic Commer ce has been constantly in cr easing in the last 15 year s, but, as a result of the massification of social net wor ks and the for ced application of electr onic tr ansaction methods as a result of Covid-19 , it is necessary for us to seek solutions to litigation. that ar e presented or will be presented to us by the development of society.To solve the above, electr onic ar bitration will be able to meet the needs of mer chants and consumer s in the execution of their contracts concluded using Infor mation and Communication Technologies (ICT)